Convergent and divergent evolution in carnivorous pitcher plant traps. Issue 3 (13th November 2017) - Thorogood, Chris J.; Bauer, Ulrike; Hiscock, Simon J.
Abstract : Contents   Summary 1035 I. Introduction 1035 II. Evolution of the pitcher 1036 III. Convergent evolution 1036 IV. Divergent evolution 1038 V. Adaptive radiation and speciation 1040 VI. Conclusions and perspectives 1040   Acknowledgements 1040   References 1040 Summary: The pitcher trap is a striking example of convergent evolution across unrelated carnivorous plant lineages. Convergent traits that have evolved across pitcher plant lineages are essential for trap function, suggesting that key selective pressures are in action. Recent studies have also revealed patterns of divergent evolution in functional pitcher morphology within genera. Adaptations to differences in local prey assemblages may drive such divergence and, ultimately, speciation. Here, we review recent research on convergent and divergent evolution in pitcher plant traps, with a focus on the genus Nepenthes, which we propose as a new model for research into adaptive radiation and speciation.